Il viaggio come martirio: santa Restituta tra Ischia e Napoli - D’Angelo, Edoardo (Kritik. Rivista di letteratura e critica culturale, 2024)
A hagiographic text in Latin written in the 10th century by Pietro Suddiacono Napoletano is dedicated to Santa Restituta, patron saint of the island of Ischia. Restituta, of African origin, arrives in Ischia at the end of a tragic journey. The Romans discover her as a Christian, and condemn her to an atrocious death: they set fire to a small boat and, placing the girl on it, they abandon the boat to the waves so Restituta arrives in Ischia already dead.